2014
DOI: 10.1371/journal.pone.0097196
|View full text |Cite
|
Sign up to set email alerts
|

S1P1 Receptor Modulation Preserves Vascular Function in Mesenteric and Coronary Arteries after CPB in the Rat Independent of Depletion of Lymphocytes

Abstract: BackgroundCardiopulmonary bypass (CPB) may induce systemic inflammation and vascular dysfunction. Sphingosine 1-phosphate (S1P) modulates various vascular and immune responses. Here we explored whether agonists of the S1P receptors, FTY720 and SEW2871 improve vascular reactivity after CPB in the rat.MethodsExperiments were done in male Wistar rats (total n = 127). Anesthesia was induced by isoflurane (2.5–3%) and maintained by fentanyl and midazolam during CPB. After catheterization of the left femoral artery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…9,10 Several studies have reported that the role of S1P/S1PR1 maintained vascular tone by eNOS activation. Samarska et al 13 have reported that the activation of S1PR1 promotes vasorelaxation responses in vessels, such as coronary artery and mesenteric artery, because of vascular NO synthesis derived from eNOS activation. Zheng et al 28 have reported that S1P, which is one of the bioactive lipids of S1PR1, protected SECs from ethanol-induced injury in primary cultures and isolated perfused rat livers, and that the protective effect of S1P was mediated by the activation of eNOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Several studies have reported that the role of S1P/S1PR1 maintained vascular tone by eNOS activation. Samarska et al 13 have reported that the activation of S1PR1 promotes vasorelaxation responses in vessels, such as coronary artery and mesenteric artery, because of vascular NO synthesis derived from eNOS activation. Zheng et al 28 have reported that S1P, which is one of the bioactive lipids of S1PR1, protected SECs from ethanol-induced injury in primary cultures and isolated perfused rat livers, and that the protective effect of S1P was mediated by the activation of eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…7 From a pharmacological point of view, S1PR1-selective agonists could serve as novel therapeutics. The development of the highly selective S1PR1 agonist, SEW2871, which was originally identified in 2004, 8 has enabled examination of S1PR1-mediated cell responses, using animal models such as renal IRI, 9,10 myocardial IRI, 11 heart transplant, 12 cardiopulmonary bypass, 13 and acute pancreatitis. 14 Using a renal IRI mouse model, Lien et al 9 revealed that SEW2871 administration significantly attenuated renal damage by reducing neutrophil/macrophage infiltration and cytokine production in the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the Akt/eNOS vasodilation pathway may be more important than cell proliferation pathway in S1PR1 selective agonist–induced collateral growth of the leptomeningeal arteries. In a previous study in a cardiopulmonary bypass rat model, in which shear stress is activated by the change in arterial pressure [ 24 ], SEW2871 enhanced coronary artery dilation by activating S1PR1 on endothelial cells, which release NO through activation of eNOS [ 25 ]. However, SEW2871 has no significant vasodilation effect on isolated rat arteries in the absence of shear stress [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…В то же время для больных, оперированных в условиях ИК или параллельного ИК в раннем послеоперационном периоде, характерно ишемическое/реперфузионное повреждение и значительная выраженность системного воспалительного ответа с нарушением баланса между про-и противовоспалительными медиаторами при сравнении с больными, оперированными на работающем сердце [19]. Системный воспалительный ответ приводит к прогрессированию эндотелиальной дисфункции со вторичным отёком и/или гипоперфузией тканей [18]. Нейтрофилы, являющиеся основной популяцией лейкоцитов, в наибольшей степени несут ответственность за развитие послеоперационных осложнений.…”
Section: Introductionunclassified